Adherence to and early adverse events of COVID-19 vaccine in a cohort of 600 Italian breastfeeding and pregnant physicians. Issue 6 (30th November 2022) - Montalti, Marco; Guaraldi, Federica; Di Valerio, Zeno; Ragghianti, Benedetta; Tedesco, Dario; Mannucci, Edoardo; Monami, Matteo; Gori, Davide
ABSTRACT: Pregnant and breastfeeding women (PBW) have been excluded from COVID-19 vaccine registry and the majority of post-marketing trials, despite the recognized increased risk of severe infections and complications. The lack of efficacy and safety data prevented the formulation of specific indications/guidelines for vaccination and could have also contributed to increased vaccine hesitancy (VH) in PBW. The aim of this cross-sectional study is to assess the rate and predictors of VH, and early adverse events (AEFI) following COVID-19 vaccine in PBW with a cross-sectional study. In January 2021, a purposely designed questionnaire was administered to 600 PBW part of a Facebook group of physicians, immunized with two doses of Comirnaty®. Thirty-eight (29%) pregnant women and 13 (2.8%) breastfeeders were hesitant. The only statistically significant negative predictor of COVID-19 VH appeared to be having had the flu shot in 2020/2021 (OR: 0.35; 95% CI: 0.13–0.97; p = .044). Approximately 27% of PBW reported hesitancy toward the 2020/2021 season influenza vaccine. Among the vaccinated subjects, 51.6% of pregnant and 75.2% of breastfeeding women reported at least one symptom after the first, and 82.4% and 81.6%, respectively, after the second dose. Nausea/vomiting, fatigue, headache and arthralgia/myalgia were the most common symptoms; dizziness, shivering, syncope and limb paresthesia were rarely reported. Among infants of breastfeeding mothers, six experienced fever, five rash and four moderate and self-limiting diarrhea. Preliminary data on mRNA COVID-19 vaccine in PBW and in their infants are reassuring since AEFI, although frequent, are typically mild and similar to those occurring in the general population, and in PBW after other vaccines. Larger studies with longer follow-up after vaccination are strongly recommended to develop recommendations in these patients.